2013
DOI: 10.1111/epi.12247
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ketamine for the treatment of refractory status epilepticus: A retrospective multicenter study

Abstract: Summary Purpose To examine patterns of use, efficacy and safety of intravenous ketamine for the treatment of refractory status epilepticus (RSE). Methods Multicenter retrospective review of medical records and EEG reports in ten academic medical centers in North America and Europe, including 58 subjects, representing 60 episodes of RSE were identified between 1999 and 2012. Seven episodes occurred after anoxic brain injury. Key findings Permanent control of RSE was achieved in 57% (34/60) of episodes. Ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
220
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(233 citation statements)
references
References 28 publications
6
220
2
5
Order By: Relevance
“…In a retrospective study of 42 patients with RSE and SRSE, (s)‐ketamine infusion for a median of 3 days resulted in a survival rate of 54.8% and resolution of SRSE in 64% of patients 48. Another retrospective case series demonstrated a 57% control rate and 57% survival rate when ketamine was administered in 58 subjects with 60 episodes, although no subject responded when ketamine was introduced 8 days beyond status epilepticus onset, compared to a large proportion of patients in our cohort responding after a 9.2‐day mean duration of status epilepticus before brexanolone administration 49. A randomized, single‐blind trial recruiting 24 patients demonstrated a 43% response rate and 57% survival rate among 14 patients assigned to propofol and a 22% response rate and a 56% survival rate among 9 patients assigned to barbiturates 50.…”
Section: Discussionmentioning
confidence: 50%
“…In a retrospective study of 42 patients with RSE and SRSE, (s)‐ketamine infusion for a median of 3 days resulted in a survival rate of 54.8% and resolution of SRSE in 64% of patients 48. Another retrospective case series demonstrated a 57% control rate and 57% survival rate when ketamine was administered in 58 subjects with 60 episodes, although no subject responded when ketamine was introduced 8 days beyond status epilepticus onset, compared to a large proportion of patients in our cohort responding after a 9.2‐day mean duration of status epilepticus before brexanolone administration 49. A randomized, single‐blind trial recruiting 24 patients demonstrated a 43% response rate and 57% survival rate among 14 patients assigned to propofol and a 22% response rate and a 56% survival rate among 9 patients assigned to barbiturates 50.…”
Section: Discussionmentioning
confidence: 50%
“…No response was observed below infusion dosages of 0.9 mg/kg/h or if the ketamine was introduced into the treatment regimen after more than 8 days since the beginning of SE. In this study, safety concerns lead to discontinuation of the infusion in four (7 %) subjects [12]. Another retrospective series on 11 adults reported RSE termination in all patients with ketamine, seven of them within 1 week of initiating ketamine treatment (2 subsequently died); SE lasted less than 8 days in all patients [13].…”
Section: Third Line Of Treatment and Beyondmentioning
confidence: 63%
“…A recent reappraisal of studies on ketamine, an N-methyl-D-aspartate (NMDA) antagonist, remind that in terms of pathophysiological considerations, this drug appears to be very promising in treating RSE. In a retrospective, multicenter assessment of 58 adults and children (60 episodes) [12], permanent RSE control was achieved in seven patients (12 %) likely due to the administration of ketamine; intriguingly, as many as four of these patients had postanoxic SE (it is unclear how many survived). No response was observed below infusion dosages of 0.9 mg/kg/h or if the ketamine was introduced into the treatment regimen after more than 8 days since the beginning of SE.…”
Section: Third Line Of Treatment and Beyondmentioning
confidence: 99%
“…Response to ketamine was shown to be better when used as a third-or fourth-line agent rather than late in the course of SRSE and when the maintenance dose was greater than 0.9 mg/kg/h. 47 Intravenous magnesium has also been used in SRSE, even in the absence of evidence of hypomagnesaemia. Its antiepileptic effect, however, has not been consistently supported in an experimental setting.…”
Section: Super-refractory Status Epilepticusmentioning
confidence: 99%